ANALYSIS OF THE ROLE AND PSYCHOLOGICAL CHARACTERISTICS OF EFFECTIVE SKILLS IN TEACHING ENGLISH - Rustamov, Ilxom; Ataboyev Isroiljon Mirza o`g`li, (Журнал иностранных языков и лингвистики, 2023)
Hearing or listening and understanding is difficult for learners because they quickly distinguish speech sounds, remember them when hearing a word, sentence, or sentence and recognize them as a sensory unit. Students can do this easily and naturally in their language and they cannot do this in a foreign language when they start learning the language.